Answer:
x = 4
Step-by-step explanation:
3x -5 = -2 + 9
-2 + 9 = 7 so now its 3x - 5 = 7
add 5 to the -5 so it cancels itself out. then add the 5 to 7 so it become 12. the you have 3x = 12
divide 12 ÷ 3 = 4
x = 4
(2y +1)(4y + 1) is the factored form
I would say it could be 35
A(5) = 2 + 5^2 = 2 + 25 = 27
Step-by-step explanation:
This sequence is defined as a(n) = 2 + n^2.
Thus, a(1) = 2 + 1^2 = 2 + 1 = 3
Then a(5) = 2 + 5^2 = 2 + 25 = 27
In a direct proportion, the equation can be set up as
y = kx
k = y/x
k = 6/20
k = 0.3